3D wind observations with a compact mobile lidar based on tropo- and stratospheric aerosol backscatter - T. H. Mense; J. Höffner; G. Baumgarten; R. Eixmann; J. Froh; A. Mauer; A. Munk; R. Wing; F.-J. Lübken (Atmospheric Measurement Techniques, 2024)
We present the first measurements of simultaneous horizontal and vertical winds using a new lidar system developed at the Leibniz Institute of Atmospheric Physics in Kühlungsborn, Germany (54.12° N, 11.77° E), for the concept of Vertical And Horizontal COverage by LIdars (VAHCOLI). We describe the technical details of a multi-field-of-view (MFOV) upgrade, which allows the measurement of wind dynamics in the transition region from microscale to mesoscale (103–104 m). The method was applied at the edge of a developing high-pressure region, covering altitudes between 3 and 25 km. Comparisons between the lidar measurements and data from the European Centre for Medium-Range Weather Forecasts (ECMWF) show excellent agreement for the meridional wind component along the north beam of the lidar, which is better than 0.30±0.33 m s−1, while along the south beam, a higher deviation with -0.93±0.73<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="64pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="b4aba4b3ac0579c465d577e9ac42284f"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-17-1665-2024-ie00001.svg" width="64pt" height="10pt" src="amt-17-1665-2024-ie00001.png"/></svg:svg> m s−1 is observed. Measurements of vertical wind show a significant underestimation of this component by ECMWF. Comparison of Aeolus winds to the lidar winds projected to the Aeolus viewing direction shows good agreement, with results better than -0.12±3.31<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="64pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="d83d005f74674675ecfeee7983e80303"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-17-1665-2024-ie00002.svg" width="64pt" height="10pt" src="amt-17-1665-2024-ie00002.png"/></svg:svg> m s−1. The capability of the MFOV lidar to explore small-scale asymmetries in the wind field is shown by a comparison of the north and south field of view, where we observe a wind asymmetry in the meridional winds, which is also present in ECMWF but underestimated by a factor of approximately 4.